Perbandingan Kinerja Keuangan Bank BNI Syariah dan BRI Syariah Sebelum dan Selama Pandemi Covid-19 - Sulaiman, Sitti Aisyah (ICOR: Journal of Regional Economics, 2022)
ABSTRACT The Covid-19 pandemic, which has spread to all countries in the world., including Indonesia, has caused the economic sector, especially the financial sector. Especially in the early cases of the Covid-19 pandemic, almost all sectors of the economy experienced paralysis. The purpose of this study was to compare the financial performance of BNI and BRI Syariah bank before and during the Covid-19 pandemic which was represented by the finance Deposit Ratio (FDR), Return on Asset (ROA), Capital Adequacy Ratio (CAR). This study uses monthly financial data, namely six months before the pandemic and six months during the pandemic. The research sample used is BNI Sharia bank and BRI sharia bank. The analytical method used in this research is to use the normality test of the data and the hypothesis using the Paired Sample t0test and the Independent Sample t-test. The result of the Paired Sample t-test showed that the FDR and CAR ratios of BNI Syariah did not have a significant difference while the ROA ratio had a significant difference. Meanwhile, the paired sample t-test of BRI banks shows that the FDR ratio does not have a significant difference, while the ROA and CAR ratios have a significant difference. Meanwhile, the result of the independent sample t-test showed that the FDR, ROA, CAR ratios had significant differences between BNI and BRI Syariah banks before the Covid-19 pandemic. Meanwhile, the independent sample t-tets for the performance of BNI and BRI during the Covid-19 pandemic showed that the FDR, ROA, and CAR ratios did not have a significant difference. Keywords: Financial Performance, Covid-19 Pandemic